Current Research On Early Childhood Education In Chile: The Quality Of The Services And Early Literacy - Carcamo Leiva, Rodrigo Alejandro; Garcia Riquelme, Alicia Alejandra (My University, 2019)
The third volume in the Early Childhood Education in the 21st Century: International Teaching, Family and Policy Perspectives miniseries focuses on research highlights and policy aspects of early childhood education and care from 22 different countries around the world. This volume provides a platform for authors to discuss and debate the implications of research findings on current practices that reflect policies of each country. The research presented spans from challenges in teacher training to case studies of family practices around early child development to problematise the key components of teacher education and family practices that impact young children's education and care. By problematising the key issues, chapter authors discuss the shifting paradigm of early childhood education and the importance of future research in informing these changes. Offering key policy and practice insights across 19 different countries, this book is a must-read for early childhood educators, researchers, early childhood organisations, policy makers and those interested to know more about early childhood within an international perspective.